2016
DOI: 10.17583/rasp.2016.1640
|View full text |Cite
|
Sign up to set email alerts
|

Do Volunteering and Charity Pay Off? Well-being Benefits of Participating in Voluntary Work and Charity for Older and Younger Adults in Finland

Abstract: Happiness and health are commonly used well-being indicators, and studies have shown that engaging in voluntary work and charity is associated with increased well-being. However, few studies have analysed the association between volunteering or charity and well-being using nationally representative data from two adult generations. Utilising the Generational Transmissions in Finland surveys collected in 2012, we examined whether volunteering and charity were associated with self-perceived happiness and health i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Research on helping behavior beyond the nuclear family has yielded a large body of literature indicating that providing voluntary support for others has beneficial effects on a the supporter's health outcomes in a variety of respects (e.g., Brown et al, 2008;Kahana et al, 2013;Morrow-Howell et al, 2003;Musick et al, 1999;Tanskanen and Danielsbacka, 2016). Concerning older adults in particular, Anderson et al (2014) reviewed 73 studies and found that, for people aged 50 years and older, volunteering was consistently associated with reduced symptoms of depression, better selfreported health, fewer functional limitations, or enhanced longevity (for similar results, see Okun et al, 2013).…”
Section: Benefits For the Older Helper: Findings From The Behavioral mentioning
confidence: 99%
“…Research on helping behavior beyond the nuclear family has yielded a large body of literature indicating that providing voluntary support for others has beneficial effects on a the supporter's health outcomes in a variety of respects (e.g., Brown et al, 2008;Kahana et al, 2013;Morrow-Howell et al, 2003;Musick et al, 1999;Tanskanen and Danielsbacka, 2016). Concerning older adults in particular, Anderson et al (2014) reviewed 73 studies and found that, for people aged 50 years and older, volunteering was consistently associated with reduced symptoms of depression, better selfreported health, fewer functional limitations, or enhanced longevity (for similar results, see Okun et al, 2013).…”
Section: Benefits For the Older Helper: Findings From The Behavioral mentioning
confidence: 99%
“…Research has shown that being charitable can increase our sense of happiness, which contributes to emotional well-being [52][53][54]. This may be of particular importance to young adults, who tend to be more idealistic and driven to make a positive impact for causes they believe in [54]. Indeed, in the present investigation, the younger cohort of respondents (18-29 year olds) were more likely than older age groups to report donating to help feed the animals during lockdown.…”
Section: How Did People Stay Connected To Zoos During Lockdown?mentioning
confidence: 55%
“…A quarter of the people who chose to stay connected to a zoo during lockdown indicated that they donated to feed the animals. Research has shown that being charitable can increase our sense of happiness, which contributes to emotional well-being [52][53][54]. This may be of particular importance to young adults, who tend to be more idealistic and driven to make a positive impact for causes they believe in [54].…”
Section: How Did People Stay Connected To Zoos During Lockdown?mentioning
confidence: 99%
“…The British Heart Foundation (2019) determined that young people are more interested in volunteering than older people. In addition, Tanskanen and Danielsbacka (2016) determined that older adults who do voluntary charity work are happier than those who do not, and young adults who donate to charities are happier than those who do not. On the other hand, Eks i et al (2016) concluded in their study that there is no difference between age and altruism.…”
Section: Jec 176mentioning
confidence: 99%